Dural Tear: A Feared Complication of Lumbar Discectomy - Albayrak, Serdal; Ozturk, Sait; Ayden, Omer; Ucler, Necati (Turkish Neurosurgical Soc, 2016)
AIM: To show causes of dural tear in isolated lumbar disc surgery, and to investigate the risk factors. MATERIAL and METHODS: We retrospectively reviewed 1159 cases (532 females and 627 males) involving patients who underwent a surgery for the treatment of lumbar disc herniation between 2006 and 2013. We have analysed the side of the surgery, level of the operation, first or revision surgery, type of anesthesia and type of surgical procedure for the risk of dural tear. To examine differences between disc levels, we used Chi-square testing for categorical variables and the student's t test for continuous variables. To analyze our data, we used STATA version 12. A p value less than 0.05 was considered as statistically significant. RESULTS: A total of 1047 (90.3%) cases were treated with microdiscectomy, and 112 (9.7%) required open discectomy. Overall, 820 (70.7%) and 339 (29.3%) surgeries were performed under epidural and general anesthesia, respectively. Dural tear ratio was 1.20%. In dural tear ratio, there was a significant difference in gender (Female: 1.6%, Male: 0.79%) (p<0.05). Dural tear ratios at primary disc surgery and at recurrent disc surgery were respectively 0.82% and 7.14% (p<0.05). Most of the tears were on the right side (11/14) (p<0.05). 13 dural tear cases (1.58%) were noted in patients who operated under epidural anesthesia (820 cases) compared to 1 (0.29%) under general anesthesia (339 cases) (p<0.05). CONCLUSION: Recurrent disc surgery, female sex, epidural anesthesia, open discectomy, non-dominant hand usage of surgeon, and upper-level affected lumbar discs were risk factors for intraoperative dural tear during lumbar disc surgery.
Keywords: Dural tear; Epidural anesthesia; Lumbar discectomy; Recurrent disc